2017
DOI: 10.1111/papr.12636
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of the Central Sensitization Inventory: A Systematic Review

Abstract: An assessment of the published measurement studies of the CSI suggest the tool generates reliable and valid data that quantify the severity of several symptoms of CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 32 publications
5
145
0
1
Order By: Relevance
“…Since the CSI was published it has been widely used in research and in clinical practice. The measurement properties have been established for the different languages versions of the CSI (Scerbo et al., ). A cutoff score has been established at 40 of 100 points (Kregel et al., ; Neblett et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the CSI was published it has been widely used in research and in clinical practice. The measurement properties have been established for the different languages versions of the CSI (Scerbo et al., ). A cutoff score has been established at 40 of 100 points (Kregel et al., ; Neblett et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies already identified the reliability, internal consistency, validity, and cutoff score for different languages (Cuesta‐Vargas, Roldan‐Jimenez, Neblett, & Gatchel, ; Kregel et al., ; Mayer et al., ; Tanaka et al., ). A systematic review showed that the CSI performs extremely well on its measurement properties (Scerbo et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…But there is growing evidence that CSI scores are associated with CS‐related symptoms and diagnoses. A recent systematic review identified 14 CSI studies, which were determined to have good‐to‐excellent quality of evidence (Scerbo et al., ). The authors concluded that the CSI generates reliable and valid data to quantify the severity of CS‐related symptoms.…”
Section: Validity Of the Csimentioning
confidence: 99%
“…Also, total CSI scores have been found to discriminate between subjects with presumably different levels of CS, including patients with chronic regional pain, widespread pain/FM, and controls . In a recent systematic review, researchers concluded that the CSI generates reliable and valid data to quantify the severity of CS‐related symptoms …”
Section: Introductionmentioning
confidence: 99%